CURCUMIN - HEALTH PROMISE FOR THE FUTURE - Chatterjee, Bandana; Modi, Kanchan; Patel, Tinkal (International Journal of Clinical and Biomedical Research, 2015)
Curcumin is a phytochemical which is extracted from Turmeric root. It is used as Ayurvedic Medicine. Curcumin (diferuloylmethane) is a yellow pigment present in the turmeric (Curcuma longa) which gives the yellow color to turmeric that has been associated with antioxidant, anti-inflammatory, anticancer, antiviral, and antibacterial activities. Curcumin, these effects are mediated through the regulation of various transcription factors, growth factors, inflammatory cytokines, protein kinases, and other enzymes. Most westerners know turmeric as gold colored Indian spice. Turmeric and curcumin are not the same thing. The antioxidant and anti-inflammatory property of curcumin is much more potent in an extracted form. In the recent research findings of curcumin that it can also eliminate 3% of cancer stem cells present inside the malignant tumor and remaining 97% of cancer cells undergo gradual cell shrinkage which ultimately leads to cell death. Pharmacologically, curcumin has been found to be safe. Human clinical trials indicated no dose-limiting toxicity when administered at doses up to 10 g/day. All of these studies suggest that curcumin has enormous potential in the prevention and therapy of various diseases. KEYWORDS: Curcumin; Phytochemical; Curcuma longa; Ayurvedic Medicine.